Pengelolaan Sampah Anorganik Melalui Alat Pembakar Sampah Alternatif untuk Mewujudkan Lingkungan Sehat - Khoir, Uray Miftahul; Wahyuni, Anggita Tri; Putri, Aida Dyah; Vembry, Angelicenia; Kartikaningsih, Hana; Salsabila, Shafa Putri; Nugroho, Duta Ardi; Ikhsan, Muhammad Fachrul; Izzadin, Muhammad Rafif; Sahida, Daffa Maulana; Muhammad, Danang Wahyu (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The waste problem in Yogyakarta, especially in Dusun Klangkapan II, is an issue that requires immediate solutions. Waste that continues to increase without proper management can cause environmental pollution, such as air, soil, and water pollution, which has the potential to endanger the health of the surrounding community. Organic and inorganic waste that is not handled properly can also cause unpleasant odors and become a breeding ground for various diseases. To overcome this problem, the Universitas Muhammadiyah Yogyakarta Community Service (KKN) team conducted a waste management program based on alternative, low-smoke waste incinerators. This program aims to educate the public about the importance of waste processing, as well as provide solutions in the form of more environmentally friendly combustion technology. The implementation of this program involves various methods such as community outreach, direct training related to the use of the tool, and regular assistance to ensure the effectiveness of its use. The alternative, low-smoke waste incinerator is designed with a multi-stage combustion system that is more efficient than conventional combustion methods. This technology helps reduce air pollution from indiscriminate waste burning, which often produces excess smoke and toxic gases. The evaluation results of this program show that the community is beginning to understand the importance of sorting and managing their waste in a more effective and environmentally friendly way. With this program, it is hoped that the people of Dusun Klangkapan II can independently manage their household waste, so that the surrounding environment becomes cleaner and healthier. Awareness and active involvement of the community in the waste management process are the keys to the sustainability of this program in the future